Paediatric eosinophilic oesophagitis in New Zealand: A 3‐year prospective study. (12th September 2020) - Roberts, Amin J; Day, Andrew S; Sinclair, Jan; Dickson, Nigel; Porter, Jody; Wellington, Grace; Evans, Helen M
Abstract : Aim: Eosinophilic oesophagitis (EoE) is a rare, chronic, relapsing immune/antigen‐mediated disease characterised by symptoms of oesophageal dysfunction, with a paucity of data among New Zealand (NZ) children. This 3‐year prospective study aimed to characterise EoE diagnosed nationally and to describe initial treatment strategies adopted. Methods: Information on new diagnoses of paediatric EoE was obtained via the New Zealand Paediatric Surveillance Unit, through monthly questionnaires. Results: From February 2014 to January 2017, 73 new cases (74% male) of EoE were reported, including 74% NZ European, 10% Asian, 7% Māori, 5% Middle‐Eastern and 3% Pacific peoples. Median age of symptom onset was 4 years; dysphagia (48%) was the most common, followed by vomiting/regurgitation (40%), food impaction (19%) and epigastric pain (16%). A co‐morbid history of other allergic conditions was present in 62% of patients, and 41% had a first degree relative with atopy. Seventy‐nine percent of patients had abnormal endoscopic findings, most commonly linear furrows and white plaques; none had strictures. Median eosinophil count per high‐powered field was 40 and 50 in the mid and distal oesophagus, respectively. Fifty‐four percent of patients were initially managed with dietary manipulation alone (four required elemental feeds, five nasogastric tubes). Fifty‐four percent of patients were treated with swallowed corticosteroids and 7% with prednisone. One patient was also treated with a leukotriene receptor antagonist. Conclusion: This first prospective study on paediatric patients with EoE in NZ finds similar demographics and disease characteristics as in other populations despite our unique ethnic population. Long‐term prospective observational data should significantly improve our knowledge of this rare condition.